Metabolic Consequences of Neuronal HIF1α-Deficiency in Mediobasal Hypothalamus in Mice - Rozjan, Azmat; Shan, Weibi; Yao, Qiaoling (Frontiers in Endocrinology, 2021)
Objective: This study aimed to investigate whether hypoxia-inducible factor 1α (HIF1α) in the neurons of the medial basal hypothalamus（MBH）is involved in the regulation of body weight balance, glucose, and lipid metabolism in mice and to explore the underlying possible molecular mechanisms. Methods: HIF1αflox/flox mice were used; adeno-associated virus that contained either cre, GFP and syn,or GFP and syn(controls) was injected in the MBH to selectively knock out HIF1α in the neurons of the MBH. Then body weight,food intake were weighed daily.The levels of blood total cholesterol (TC)、triglyceride (TG)、free fatty acid (FFA) was examined. insulin-stimulated Akt phosphorylation in the liver , epididymal fat and mRNA expression levels of HIF1α,proopiomelanocortin(POMC),and neuropeptide Y(NPY) in the hypothalamus were tested.Results: After selectively knocking out HIF1α in the neurons of the MBH, the body weights and food intake of the mice increased significantly compared with the control group (P <0.001 at 4 weeks).Compared with the control group, the insulin level was 3.5 times higher (P <0.01). The results of the IPGTT experiment showed that the blood glucose level of the cre group at 20-120 min was significantly higher than the control group (P <0.05). ITT experimental results showed that the blood glucose level of the cre group was significantly higher at 20–120 min than that of the control group (P <0.05). The serum TC and FFA content was significantly higher than the control group (P<0.05). Western blot results showed that compared with the control group, the insulin-induced AKT phosphorylation in the liver and epididymal fat of the cre group did not increase significantly. RT-PCR results in the hypothalamus showed that the mRNA expressions of HIF1α, POMC, and NPY of the cre group did not significant change. Conclusions: The hypothalamic neuronal HIF1α plays an important role in the regulation of body weight balance in mice under normoxic conditions. In the absence of hypothalamic neuronal HIF1α, mice gained body weight with increased appetite, abnormal glucose, and lipid metabolism.